1975
DOI: 10.1530/jrf.0.0450073
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Electrical Activity of the Oviduct and the Uterus of the Rabbit in Vivo

Abstract: The electrical activity of the whole genital tract of the rabbit was recorded by means of chronically implanted electrodes after section of the uterotubal junction on one side. When the junction was intact, the activity of the isthmus and that of the proximal uterine horn occurred almost simultaneously, but uterine activity decreased after the junction was cut. During the preovulatory phase and also after administration of HCG, synchronos activity due to adrenergic drugs, smoke or oxytocin persisted on both si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…In this research, there were no differences in mechanical and electrical activity between different segments of the rabbit uterus. Basal values of electrical activity (intensity) of the tube (0.119 mV, non transformed data) are similar to those reported previously (0.100-0.200 mV); in contrast, values obtained from the uterine horn are lower: 0.158 mV (non transformed data) vs. 0.200-0.250 mV (Ruckebusch, 1975). It should be noted that the data were recorded during the pre-ovulatory phase in both cases; it has been reported that the uterine motility of many species undergoes pattern changes throughout the estrous cycle (Ruckebush and Bueno, 1976;Coy et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this research, there were no differences in mechanical and electrical activity between different segments of the rabbit uterus. Basal values of electrical activity (intensity) of the tube (0.119 mV, non transformed data) are similar to those reported previously (0.100-0.200 mV); in contrast, values obtained from the uterine horn are lower: 0.158 mV (non transformed data) vs. 0.200-0.250 mV (Ruckebusch, 1975). It should be noted that the data were recorded during the pre-ovulatory phase in both cases; it has been reported that the uterine motility of many species undergoes pattern changes throughout the estrous cycle (Ruckebush and Bueno, 1976;Coy et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Sperm release seems to be related to the combined effects of signalling between oviductal cells and the oocyte, progesterone levels, parallel capacitation events and changes in the levels of different molecules involved in the binding of sperm to oviduct that may vary throughout estrous cycle (for review see, Coy et al, 2012). Previous research on uterine motility has been focused on establishing interactions between electrical and mechanical characteristics of rabbit oviductal smooth muscle and between longitudinal and circular muscle (Talo, 1974;Ruckebusch, 1975;Coons and Johns, 1982). Analysis of the electrical spiking activity of the ewe oviduct and uterus during natural and induced estrus has also been examined (Ruckebusch and Bueno, 1976), as well as the effects of hormonal manipulation on the rabbit oviduct isthmus motility with the aid of special transducers (Muller and Nelsen, 1979;Bourdage and Halbert, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Talo & Kekäläinen (1976) examined electrical activity of the hen oviduct in vitro, but electromyographic techniques have not been used for the genital tract in vivo, although electromyographic explorations of the digestive tract in conscious hens (Roche & Decerprit, 1977) have shown that the birds are tolerant of the presence of chronic electrodes. Electromyographic study of the oviduct and uterus in mammals has shown that there are two basic components: bursts of spike potentials linked with the mechanical events and slow waves appearing with a decreased frequency from the ovarian end towards the cervix which are re¬ lated to hormonal levels (Ruckebusch, 1975;Roche & Brard, 1976;Ruckebusch & Bueno, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…1,2,6 Animal and human studies have demonstrated effects on oviductal function resulting from smoke exposure. Inhalation of smoke has been reported to affect the electrical activity of the rabbit oviduct, 7 to reduce the ratio of ciliated to secretory epithelial cells in the hamster oviduct, and to temporarily influence patency of human Fallopian tube. 9 Despite these findings, the exact mechanism by which smoking leads to tubal ectopic pregnancy remains unknown.…”
mentioning
confidence: 99%